1998
DOI: 10.1080/00926239808414663
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Induced by Serotonin Reuptake Antidepressants

Abstract: Serotonin reuptake inhibitor (SRI) antidepressants have been associated with sexual dysfunction, though there have been few prospective reports specifically examining this problem. The purpose of this study was to determine if three SRIs affected sexual function in patients with an anxiety disorder or major depressive disorder over a 3-month period. Sixty-one patients were evaluated for at least 2 months in a prospective study of the effects of fluoxetine, sertraline, and paroxetine on five aspects of sexual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(31 citation statements)
references
References 3 publications
0
29
0
2
Order By: Relevance
“…1 Orgasm delay, anorgasmia, delayed ejaculation and impotence are commonly observed in men and women under SSRI treatment. 2 Furthermore, some degree of erectile dysfunction secondary to SSRI administration appears in more than 40% of men. 3 Sexual alterations usually disappear when the treatment is interrupted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Orgasm delay, anorgasmia, delayed ejaculation and impotence are commonly observed in men and women under SSRI treatment. 2 Furthermore, some degree of erectile dysfunction secondary to SSRI administration appears in more than 40% of men. 3 Sexual alterations usually disappear when the treatment is interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…4 Paroxetine is a representative compound of the SSRI class that has been extensively used in the clinical practice 5 and, like other compounds of its class, has been reported to induce sexual dysfunction. [1][2][3]6 It is able to inhibit in vitro and in vivo the synthesis of nitric oxide (NO) 7 which is a key mediator of penile smooth muscle relaxation and penile erection. 8,9 We have previously reported that paroxetine impairs erectile responses to cavernosal nerve stimulation in rats when administered either chronically or acutely.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it appeared that sexual side effects were more common in men than women. However, more recent studies have found similar rates of SSRI-induced sexual dysfunction in both sexes (47,48). Clinical series and studies in men only suggest that the SSRIs as a class cause orgasmic delay (49).…”
Section: Antidepressantsmentioning
confidence: 98%
“…In healthy volunteers, the only adverse effect attributable to indalpine was EjD which was spontaneously reported by 67% of the subjects [Seppälä et al 1988]. In men treated for depression, delay in ejaculation and orgasmic dysfunction are the most significant sexual complications [Labbate et al 1998]. Initiation of treatment results in worsening of orgasm delay, orgasm satisfaction and overall sexual functioning [Piazza et al 1997].…”
Section: In Patients On Drug Treatment For Other Conditionsmentioning
confidence: 99%